2011
DOI: 10.3109/02699052.2010.541898
|View full text |Cite
|
Sign up to set email alerts
|

From health care to home community: An Aboriginal community-based ABI transition strategy

Abstract: Findings demonstrate that the structure of rehabilitation and discharge processes for Aboriginal clients living on reserves or in remote communities are of great concern and warrants further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…A limited number of studies in this review included populations from Australia and Canada. While a limited number of studies were particular to TBI among Indigenous people from both countries, two studies from Canada 48,49 and two studies from Australia 50,51 -which did not meet the review criteriafocused on rehabilitation and/or community outreach programs particular to acquired brain injury There is a paucity of research concerning Indigenous perspectives of TBI. Given the distinct perspectives around healing and rehabilitation in terms of Indigenous populations, further research around Indigenous understandings of TBI and TBI rehabilitation are warranted.…”
Section: Tbi Rehabilitation Outcomesmentioning
confidence: 99%
“…A limited number of studies in this review included populations from Australia and Canada. While a limited number of studies were particular to TBI among Indigenous people from both countries, two studies from Canada 48,49 and two studies from Australia 50,51 -which did not meet the review criteriafocused on rehabilitation and/or community outreach programs particular to acquired brain injury There is a paucity of research concerning Indigenous perspectives of TBI. Given the distinct perspectives around healing and rehabilitation in terms of Indigenous populations, further research around Indigenous understandings of TBI and TBI rehabilitation are warranted.…”
Section: Tbi Rehabilitation Outcomesmentioning
confidence: 99%
“…Logically, a supportive social network influences participation in therapy (Sander et al, 2009; Turner et al, 2009b; Keightley et al, 2011), for example by providing transportation, accompaniment to therapies, supervision for recommended regimens for which safety is of concern (e.g., a gym program). Turner et al (2007) found that those who had more supportive and closer networks at home had better transitions from the hospital setting to the home environment, as this was related to more access to social activities and transportation outside the home.…”
Section: Post-discharge Experiences and Environmental Enrichmentmentioning
confidence: 99%
“…Several studies have indicated that the most often-reported barrier is adequate preparation prior to discharge (Rotondi et al, 2007; Sander et al, 2009; Keightley et al, 2011; Sander et al, 2011; Turner et al, 2011b). Many TBI survivors and their caregivers report that they were not given enough information regarding brain injuries (e.g., behavioral sequelae), how to access community resources (e.g., rehabilitation, emotional support, respite services), or how to access or implement home therapies (Rotondi et al, 2007; Sander et al, 2009, 2011; Keightley et al, 2011; Turner et al, 2011b).…”
Section: Post-discharge Experiences and Environmental Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant body of literature also demonstrates disparities both in access to appropriate rehabilitation services and in outcome in indigenous and other 'minority cultures' in other parts of the world (Arango-Lasprilla & Kreutzer, 2010;Arango-Lasprilla et al, 2007;Faleafa, 2009;Haider et al, 2007;Jamieson, Harrison, & Berry, 2008;Keightley et al, 2009Keightley et al, , 2011Nelson, Rhodes, Noona, Manson, & AI-SUPERPFP Team, 2007). Overall, these factors highlight the need for culturally appropriate investigation of whānau knowledge about traumatic brain injury in mokopuna.…”
Section: International Literature On Culture and Tbimentioning
confidence: 99%